1997
DOI: 10.1038/nbt0597-462
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo gene delivery mediated by a synthetic polycationic amino polymer

Abstract: A synthetic polyamino polymer with a glucose backbone was used for gene transfer in vitro and in vivo. Gene transfer in vitro to various human carcinoma cell lines was achieved with an efficiency superior to a commercially available cationic liposome preparation. The polymer was resistant to inhibition by serum, which allowed for efficient gene transfer in vivo. Direct Intracranial tumor injection using this reagent resulted in reporter gene expression levels comparable to those achieved by a recombinant adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 22 publications
1
50
0
2
Order By: Relevance
“…In general, transfections were carried out in serum-free media (Opti-MEM I Reduced Serum Media). 13,64 Briefly, the cells were washed and 300 l of the indicated polyplex formulations was added per well. After 5 h incubation, the formulations were removed and 1 ml of complete culture medium was added.…”
Section: In Vitro Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…In general, transfections were carried out in serum-free media (Opti-MEM I Reduced Serum Media). 13,64 Briefly, the cells were washed and 300 l of the indicated polyplex formulations was added per well. After 5 h incubation, the formulations were removed and 1 ml of complete culture medium was added.…”
Section: In Vitro Gene Transfermentioning
confidence: 99%
“…Ideally, such polymers should have well-defined chemical characteristics and possess the following properties: (1) a DNA-condensing capacity that generates complexes that are sufficiently small to allow an even tissue distribution and subsequent endocytosis; (2) endosomolytic properties that allow endosomal escape of the DNA; (3) biocompatibility; (4) simple synthesis and purification that allows largescale manufacture; and (5) functional groups that allow simple coupling of extracellular and intracellular targeting ligands. [9][10][11][12] A survey of the literature indicated that chemically modified cationic polysaccharides such as APL PolyCat57 13 and chitosan 12,14 may fulfil many of these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Two major forms of non-viral vectors are polyplex (complex of pDNA and cationic polymer) and lipoplex (complex of pDNA and cationic liposomes). These are independently effective for gene delivery in several cell lines and in vivo experiments (Gao et al, 1995;Goldman et al, 1997;Sorgi et al, 1997). Recently, a ternary complex of cationic polymer, cationic liposomes, and pDNA, named lipopolyplex, has been developed as a second-generation non-viral vector.…”
Section: Introductionmentioning
confidence: 99%
“…The charge-dependence of the transvascular transport is especially important for gene delivery to tumours, using polycationic liposomes (Gao and Huang, 1995) or amino polymers (Goldman et al, 1997). These non-viral vectors have shown promising results in gene delivery across the cell membrane (Gao and Huang, 1995;Goldman et al, 1997).…”
mentioning
confidence: 99%
“…The charge-dependence of the transvascular transport is especially important for gene delivery to tumours, using polycationic liposomes (Gao and Huang, 1995) or amino polymers (Goldman et al, 1997). These non-viral vectors have shown promising results in gene delivery across the cell membrane (Gao and Huang, 1995;Goldman et al, 1997). Recently, Thurston et al (1998) demonstrated that cationic liposomes are preferentially taken up by angiogenic tumour endothelium, mostly through vesicular organelles.…”
mentioning
confidence: 99%